S48 Understanding the impact of introducing a best practice tariff on clinical process standards in the national COPD audit programme. (December 2018) - Mortier, K; Stone, RA; McMillan, V; Stone, P; Holzhauer-Barrie, J; Quint, JK; Roberts, CM
Abstract : Background: On 1/2/17, the National COPD Audit moved to continuous data collection for a small number of clinical process items with real time feedback presented as run charts designed to support site level quality improvement initiatives. In addition, a best practice tariff (BPT) for COPD admissions was agreed with NHSE to promote hospital management and Board engagement with audit improvement aims. We hypothesised that there would be differences observed in the compliance of clinical process standards for the 2 process items aligned to the BPT compared with the 4 that were not. Methods: Data were entered by each site for all eligible cases in hospitals in England and Wales to a bespoke web tool hosted by Crown Informatics. Data on the following key indicators were collected: Patients receiving NIV within 3 hours of arrival, Current smokers prescribed smoking cessation pharmacotherapy, Patients with spirometry result available, Patients prescribed oxygen to target saturation, Patients receiving a discharge bundle, Patients receiving respiratory review by a member of the respiratory team within 24 hours of admission, Patients where care meets best practice tariff (BPT) for COPD; the latter three being related to the BPT. The BPT was launched on 1 st April 2017. Compliance with clinical process standards was calculated for all cases discharged during the month of February 2017; pre BPT launch, and at the end of the observation period (June 2018), after the BPT had been introduced. The proportion of hospital discharges where the clinical process standard was met were measured. Results: Data on 98, 506 COPD hospital admissions were entered by 186 hospitals over the 17 months. 4797 cases were discharged in February 2017 and 2804 in June 2018. There were improvements in compliance with all the clinical process standards measured (table 1). Conclusions: Clinical process standards linked to the BPT demonstrated a much larger degree of improvement than those not linked to the tariff. Evidence from previous studies suggests that improvement linked to financial incentives may not be sustained in the long term. Further monitoring will be required to determine if this has been a useful improvement tool for COPD care.